Perencanaan Lanskap Daya Tarik Wisata Pantai Melasti, Desa Ungasan, Kecamatan Kuta Selatan, Badung - Pawitra, Luh Putu Yulia Pradnya; Yusiana, Lury Sevita; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023, 2023)
Melasti Beach Tourism Attractions Landscape Planning, Ungasan Village, South Kuta District, Badung. Melasti Beach is one of the natural tourist attractions in Badung Regency which is used for tourism activities and socio-religious activities. The increasing number of tourism activities in Melasti Beach demands that landscape arrangement must takes into account the biophysical and socio-religious aspects in it. The purpose of this research is to make a planning of the Melasti Beach landscape that is harmonious between biophysical and socio-religious aspects. The method used is a survey with data collection techniques through observation, interviews and literature study. The research stages in this planning consist of preparation, inventory, analysis, synthesis and landscape planning. Analysis and synthesis of data was carried out spatially using an assessment level with the help of a Geographic Information System (GIS) to obtain three spatial zones that refer to the Tri Mandala concept, consisting of zones for tourism use, buffers and religious sacred ones. The circulation plan is divided into primary and secondary circulation paths with the circulation designation for Visitors with Religious Interests (PDKK) and tourists on each circulation path. The main activity plan consists of tourism activities and religious activities.